Recuperación de la memoria histórica del fútbol barrial a través del testimonio oral de sus actores. Estudio de caso liga la Tola - Tipán Lema, Andrés Eduardo (2014)
In society, football is one of the sports that moves large numbers of people at a particular time, is a vehicle for communication, a filter, an ideal space that allows observing the different social relations, which are transformed and reconfigured during a period of relative and transient time valuably. . This study aims to visualize the neighborhood football capital, through League La Tola and especially by the oral testimony of its actors. The qualitative research will recover historical memory supported with the theoretical part, which is the fundamental basis of the above work. Concepts such as Communication, Culture, and Football neighborhood relate to the Historical Memory. Communication for Development and Alternative Communication and Identities encompassing this traditional sport will also be addressed.